2021
DOI: 10.1111/pin.13132
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative pathology consultation during urological surgery: Impact on final margin status and pitfalls of frozen section diagnosis

Abstract: Despite recent improvements in diagnostic and surgical techniques in urological oncology, positive resection margin remains a significant concern for surgeons. Meanwhile, intraoperative pathology consultation with frozen section assessment (FSA), particularly for histological diagnosis of the lesions incidentally found or enlarged or sentinel lymph nodes, generally provides critical information which enables immediate decision making for optimal patient care. The intraoperative evaluation of surgical margins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Intraoperative frozen section analysis is a more accurate detection method and a key tool for BCS ( 9 ). However, it has disadvantages such as being time-consuming and labor-intensive ( 11 , 29 ). Previous studies have shown that the use of ICG can be used to identify tumors and normal tissues in colon cancers ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative frozen section analysis is a more accurate detection method and a key tool for BCS ( 9 ). However, it has disadvantages such as being time-consuming and labor-intensive ( 11 , 29 ). Previous studies have shown that the use of ICG can be used to identify tumors and normal tissues in colon cancers ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a few studies ( 8 , 11 , 12 , 15 , 18 , 22 , 25 , 26 , 30 , 31 , 36 , 38 ) have mentioned the use of frozen section assessment (FSA) in surgery. However, Miyamoto’s ( 58 ) study suggested that the diagnostic accuracy of FSA in partial nephrectomy and its impact on the status of the incision margin had not been determined. They did not believe that FSA will benefit patients.…”
Section: Discussionmentioning
confidence: 99%
“…Current techniques for evaluating margin statuses, such as frozen section, imprint cytology, and intraoperative ultrasound, are very useful tools for precision surgery but expensive in terms of time and costs and not always available to surgeons. Furthermore, not all hospitals have experts in the use of this instrumentation applied to tumours [ 5 , 6 ]. However, there is a clinical need for safe and accurate approaches to defining tumour margins intraoperatively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%